Characterizing the Interfacial Properties of Hfo2/Si And HfSiO/Si Gate Stacks - S. Y. Tan (The Minerals, Metals and Materials Society, 2009)
As CMOS devices are scaled down into nano-region, SiO2 dielectric is approaching its physical and electrical limits. High-k material has been investigated widely in recent years, and gate oxide take place growth oxide with Hf-based below 45nm gate length technology node has been shown. The phenomenon of interfacial property between bulk silicon and gate dielectric materials (HfO2 and HfSiO) was focused. A comparison of capacitance-voltage (C-V) characteristic of gate insulator was presented. Furthermore, the electrical property and thermal stability of high-k dielectric materials at various post deposit anneal (PDA) temperatures were established. The X-Ray diffraction technique was (XRD) utilized to analyze crystallization of the thin films, and the X-ray photoelectron spectroscopy (XPS) was applied for surface chemical bounding energy to identify the silicon and dielectric layers. Results show that HfSiO films have exhibited a superior performance on both thermal stability and electrical performance.